2019
DOI: 10.1161/circoutcomes.119.005675
|View full text |Cite
|
Sign up to set email alerts
|

Joint Shock/Death Risk Prediction Model for Patients Considering Implantable Cardioverter-Defibrillators

Abstract: Background: The risk of death or appropriate therapy varies widely among recipients of implantable cardioverter-defibrillators (ICDs). The goals of this study were to develop a risk prediction tool that jointly considers future outcome probabilities of ICD shock and death. Methods and Results: We performed a secondary analysis of patients receiving ICDs as part of the SCD-HeFT trial (Sudden Cardiac Death in Heart Failure Trial). We applied an illness-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Nonetheless, our findings raised key questions about the utility of NT-proBNP in the risk stratification of SCD. According to current guidelines (6, 7), a lot of HF patients implanted with ICDs would not receive appropriate ICD shock in the long-term follow-up (8)(9)(10)(11). Consequently, there is an urgent need to find a new risk stratification marker in addition to LVEF and NYHA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, our findings raised key questions about the utility of NT-proBNP in the risk stratification of SCD. According to current guidelines (6, 7), a lot of HF patients implanted with ICDs would not receive appropriate ICD shock in the long-term follow-up (8)(9)(10)(11). Consequently, there is an urgent need to find a new risk stratification marker in addition to LVEF and NYHA.…”
Section: Discussionmentioning
confidence: 99%
“…According to current guidelines ( 6 , 7 ), a lot of HF patients implanted with ICDs would not receive appropriate ICD shock in the long-term follow-up ( 8 11 ). Consequently, there is an urgent need to find a new risk stratification marker in addition to LVEF and NYHA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although less familiar than competing risks, semi-competing risks arise in a wide range of clinical settings including: Alzheimer's disease, as illustrated in this paper; graft-versushost disease among patients who have undergone hematopoietic stem cell transplantation for leukemia [8]; readmission following discharge from a hospitalization during which a patient is diagnosed of a terminal disease such as pancreatic cancer [21,20]; shock among patients with implanted cardiac devices [32]; and, preeclampsia a severe pregnancy-associated disease that affects between 3-10% of all pregnancies [16]. A distinguishing feature of semicompeting risks, relative to competing risks, is that there is at least partial information about the joint distribution between T 1 and T 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, LVEF being the sole determinant of guiding ICD implantation has proven to be inadequate in multiple subsequent studies. Studies have shown the majority of patients experiencing SCD have LVEF > 35% [6,7], and a high proportion of patients implanted with ICDs do not receive an ICD shock even before death [8]. In terms of patient outcomes, the 2016 DANISH trial [9] showed that prophylactic ICD implantation in patients with symptomatic non-ischaemic heart failure and LVEF < 35% was not associated with a significant reduction in mortality.…”
Section: Editorial Commentarymentioning
confidence: 99%